1996
DOI: 10.1007/bf00143393
|View full text |Cite
|
Sign up to set email alerts
|

A cellular model for drug interactions on hematopoiesis: The use of human umbilical cord blood progenitors as a model for the study of drug-related myelosuppression of normal hematopoiesis

Abstract: A cellular model of hematopoiesis which would be more convenient than bone marrow (BM) progenitors and directly relevant to human pathology is needed in order to investigate xenobiotic toxicity. Human umbilical cord blood (HCB), previously shown to be able to repopulate BM, provides a powerful in vitro model of normal human hematopoiesis. In order to validate the use of normal HCB progenitors as targets for dose-related myelosuppression, we used clonogenic assays and expansion in a liquid culture of progenitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…To obtain data on the sensitivity of haematopoietic progenitors, we first performed in vitro myelotoxicity experiments testing IDR, IDRol, and doxorubicin as a reference compound. We used HCB as a source of haematopoietic progenitors as suggested by Leglise et al (1996) and Ghielmini et al (1997Ghielmini et al ( , 1998. The experiments with doxorubicin produced results similar to the published ones (Minderman et al, 1994;Ghielmini et al, 1998).…”
Section: mentioning
confidence: 66%
“…To obtain data on the sensitivity of haematopoietic progenitors, we first performed in vitro myelotoxicity experiments testing IDR, IDRol, and doxorubicin as a reference compound. We used HCB as a source of haematopoietic progenitors as suggested by Leglise et al (1996) and Ghielmini et al (1997Ghielmini et al ( , 1998. The experiments with doxorubicin produced results similar to the published ones (Minderman et al, 1994;Ghielmini et al, 1998).…”
Section: mentioning
confidence: 66%
“…Our approach to explore whether oxygen radicals are involved in endotoxin-mediated neonatal granulocytopenia is based on the HUCB model from which granulopoiesis and granulocyte apoptosis may be monitored in vitro. Using a similar model, Leglise et al (5). showed that CFU-GM formation from HUCB provided a useful model for the evaluation of myelosuppression by xenobiotics, which was comparable to in vivo situations.…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain whether sepsis-induced oxygen radicals can cause a decrease in granulocyte growth or promote an increase in granulocyte destruction in neonates. Others have demonstrated that an in vitro HUCB model is useful for assessing the effects of drugs and biochemicals on hematopoiesis (5,6). Granulocyte apoptosis can also be assessed by the detection of early cell surface exposure of phosphatidylserine (PS) and late DNA fragmentation (7,8).…”
mentioning
confidence: 99%
“…Haematopoietic stem and precursor cells are normally present in fetal blood and were shown to share many features with BM cells (Hows et al, 1992), although some immunophenotypic and in vitro growth characteristics are not completely superimposable (Hao et al, 1995;Fritsch et al, 1996). Recently, Leglise et al (1996) demonstrated the equivalence of both stem cell sources for in vitro myelotoxicity tests for several classes of drugs, including anticancer, antibiotic and antiviral drugs. Experiments performed in our laboratory with doxorubicin and other anthracyclines produced very similar results on hCB and on BM (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%